2019
DOI: 10.1186/s13287-019-1224-y
|View full text |Cite|
|
Sign up to set email alerts
|

Priming approaches to improve the efficacy of mesenchymal stromal cell-based therapies

Abstract: Multipotent mesenchymal stromal cells (MSC) have been widely explored for cell-based therapy of immune-mediated, inflammatory, and degenerative diseases, due to their immunosuppressive, immunomodulatory, and regenerative potentials. Preclinical studies and clinical trials have demonstrated promising therapeutic results although these have been somewhat limited. Aspects such as low in vivo MSC survival in inhospitable disease microenvironments, requirements for ex vivo cell overexpansion prior to infusions, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
410
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(423 citation statements)
references
References 164 publications
(253 reference statements)
8
410
0
5
Order By: Relevance
“…The cargo of USMSC-EVs in this study contained many chemokines (CXCL5, CCL3, CCL4, CCL11, CCL20), which might attract immune cells to the site of injury. However, research has strongly shown that MSCs primed with pro-inflammatory cytokines (IFN-γ, TNF-α, IL-1β) show enhanced immunosuppressive abilities [14,[21][22][23]. Specifically, research using EVs secreted from pro-inflammatory primed MSCs has shown positive immunosuppressive effects by polarising pro-inflammatory immune cells into anti-inflammatory immune cells in vitro [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cargo of USMSC-EVs in this study contained many chemokines (CXCL5, CCL3, CCL4, CCL11, CCL20), which might attract immune cells to the site of injury. However, research has strongly shown that MSCs primed with pro-inflammatory cytokines (IFN-γ, TNF-α, IL-1β) show enhanced immunosuppressive abilities [14,[21][22][23]. Specifically, research using EVs secreted from pro-inflammatory primed MSCs has shown positive immunosuppressive effects by polarising pro-inflammatory immune cells into anti-inflammatory immune cells in vitro [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significant difference in growth kinetics of protein cargo between UCMSCs grown in normoxia and hypoxia, and research was divided on whether hypoxia has a stimulatory [30] or inhibitory [31,32] effect on MSC proliferation; albeit studies varied between the use of 1%-5% O 2 . Some groups have advocated for the use of hypoxia when growing cells in culture as it more closely mimics the oxygen levels that MSCs are exposed to in vivo [22], with neonatal-derived tissues rarely exceeding 5% in vivo [23]. The lack of change in growth may be because the cells were first isolated under normal oxygen (21%) conditions, and exposure to low oxygen (5%) at an earlier stage may be an influencing factor in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, priming approaches to increase the therapeutic potential of MSCs have been investigated. Priming (also referred to as licensing or preconditioning) with pro-inflammatory mediators consists of preparing cells for some specific function or lineage-specific differentiation, which involves cell activation, molecular signaling, genetic, or epigenetic modifications [16]. This strategy is effective in promoting immunoregulatory properties when compared to unprimed cells; indeed, adipose tissue-derived MSCs are not able to inhibit proliferation of PBMCs without exposure to IFN-γ indicating that inhibitory factors are released on MSC activation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies indicate that MSCs need to be licensed by inflammatory stimuli, such as tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), and interleukin-1 α/β, to exert or improve their immunosuppressive actions [14]. Thus, in recent years, several studies have evaluated whether preconditioning bone marrow-derived MSCs cultured in vitro with IFN-γ and TNF-α could elicit a stronger immunosuppressive activity [4,[15][16][17]. IFN-γ induces a transient expression of indoleamine-2,3 dioxygenase (IDO) which inhibits T cell activation, proliferation, and functionality due to L-tryptophane depletion [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation